2015
DOI: 10.1103/physrevb.91.100407
|View full text |Cite
|
Sign up to set email alerts
|

Trimerized ground state of the spin-1 Heisenberg antiferromagnet on the kagome lattice

Abstract: We study the phase diagram of the spin-1 quantum bilinear-biquadratic antiferromagnet on the kagome lattice, using exact diagonalization (ED) and the density matrix renormalization group (DMRG) algorithm. The SU(3) symmetric point of this model Hamiltonian is a spontaneously trimerized state whose qualitative nature persists even at the Heisenberg point, a finding that contrasts previous proposals. We report the ground state energy per site of the Heisenberg model to be −1.410(2) and establish the presence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
51
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 44 publications
10
51
2
Order By: Relevance
“…I, the S = 1 Heisenberg model on the kagome lattice has recently attracted strong attention. Older proposals for the ground state, including the hexagonal singlet solid [22] and the resonating AKLT loop state [23,24], appear to have been supplanted by a trimerized simplex-solid state [25][26][27], which has the best variational energy, E k 0 = −1.4116(4) [26]. This is a symmetry-broken state with trimerization order, which as above can be defined by the difference of the average energies between up-and down-triangle simplices, quoted in Ref.…”
Section: B S =mentioning
confidence: 99%
See 1 more Smart Citation
“…I, the S = 1 Heisenberg model on the kagome lattice has recently attracted strong attention. Older proposals for the ground state, including the hexagonal singlet solid [22] and the resonating AKLT loop state [23,24], appear to have been supplanted by a trimerized simplex-solid state [25][26][27], which has the best variational energy, E k 0 = −1.4116(4) [26]. This is a symmetry-broken state with trimerization order, which as above can be defined by the difference of the average energies between up-and down-triangle simplices, quoted in Ref.…”
Section: B S =mentioning
confidence: 99%
“…Recently, and in part with a view to solving this conundrum, more attention has also been paid to kagome Heisenberg antiferromagnets with higher spins [20,21]. Various proposals have been put forward for the spin-1 case, including the hexagonal singlet solid state [22], the resonating AKLT loop state [23,24], and the trimerized simplex-solid state [25][26][27], among which the last has the best variational energy [26,27]. For the S = 2 case, a coupled-cluster calculation suggested that the ground state has √ 3 × √ 3 antiferromagnetic order [28], whereas the infinite Projected Entangled Pair States (iPEPS) algorithm indicates a (topologically trivial) spin liquid with a spin gap and no symmetry breaking [21].…”
Section: Introductionmentioning
confidence: 99%
“…The physics of the spin-one cousin of the Heisenberg model on the kagome lattice has been focused on recently [3][4][5][6][7][8][9] . Interestingly, several works point towards a spontanenous trimerization of the system 7-9 , i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the high spin (S > 1/2) kagome physics has also gained great interest currently. For the spin-1 KHAF, the ground state was shown to be a nonmagnetic simplex valence bond crystal with geometric inversion symmetry breaking [13][14][15][16][17][18]. For the spin-S KHAF, the magnetization curves [19] up to S = 2 have been obtained with tensor network methods based on the infinite projected entangled pair states (iPEPS) [20,21].…”
Section: Introductionmentioning
confidence: 99%